77.0k views
4 votes
Solve the equation
Y = -2(x+4) + 6 when x = -2 then use that value of y to evalute w = -3 - 2y

User TPG
by
5.0k points

2 Answers

5 votes

Answer:

y=8 and w=13

Explanation:

y=-2(x+4)

-2x-2=4 sooo...

y=4+4

y=8

then plug 8 into the equation for w

w=-3-2y

then you would get

w=-3-16

-3-16

w=13

User Kelvin Kantaria
by
5.7k points
0 votes

Answer:

12

Explanation:

Plug in for x first:

Y = -2(x+4) +6

Y = -2((-2)+4) +6

Y = -4 + 6

Y = 2

Then use Y to find W;

W = -3 -2y

W = -3 - 2(2)

W = -3(-4)

W= 12

User Dwayne Robinson
by
4.5k points